Role of gastrocnemius activation in knee joint biomechanics: gastrocnemius acts as an ACL antagonist. Issue 4 (11th March 2016) - Adouni, M.; Shirazi-Adl, A.; Marouane, H.
Abstract : Gastrocnemius is a premier muscle crossing the knee, but its role in knee biomechanics and on the anterior cruciate ligament (ACL) remains less clear when compared to hamstrings and quadriceps. The effect of changes in gastrocnemius force at late stance when it peaks on the knee joint response and ACL force was initially investigated using a lower extremity musculoskeletal model driven by gait kinematics—kinetics. The tibiofemoral joint under isolated isometric contraction of gastrocnemius was subsequently analyzed at different force levels and flexion angles (0°–90°). Changes in gastrocnemius force at late stance markedly influenced hamstrings forces. Gastrocnemius acted as ACL antagonist by substantially increasing its force. Simulations under isolated contraction of gastrocnemius confirmed this role at all flexion angles, in particular, at extreme knee flexion angles (0° and 90°). Constraint on varus/valgus rotations substantially decreased this effect. Although hamstrings and gastrocnemius are both knee joint flexors, they play opposite roles in respectively protecting or loading ACL. Although the quadriceps is also recognized as antagonist of ACL, at larger joint flexion and in contrast to quadriceps, activity in gastrocnemius substantially increased ACL forces (anteromedial bundle). The fact that gastrocnemius is an antagonist of ACL should help in effective prevention and management of ACL injuries.